Illicit Schemes : Fossil Fuel Subsidy Reforms and the Role of Tax Evasion and Smuggling - Rentschler, Jun; Hosoe, Nobuhiro (World Bank, Washington, DC, 2022)
This study develops a computable general equilibrium model for Nigeria, which accounts for informality, tax evasion, and fuel smuggling. By studying the impact of fuel subsidy reform on consumption, tax incidence, and fiscal efficiency, it shows that the presence of illicit activities substantially strengthens the argument in favour of subsidy reform: First, fuel subsidy reform can shift the tax base to energy goods, which are less prone to tax evasion losses than for instance labour. Second, by reducing price differentials with neighbouring countries, subsidy reform reduces incentives for fuel smuggling. Overall, the results show that considering illicit activities reduces the welfare losses of fuel subsidy reform by at least 40 percent. In addition, fuel subsidy reductions (and by extension energy tax increases) have a strong progressive distributional impact. The findings hold under different revenue redistribution mechanisms, in particular uniform cash transfers and the reduction of pre-existing labour taxes.